Parallelized tree–code for clusters of personal computers - Viturro, Hector Ruben (2000)
We present a tree-code for integrating the equations of the motion of collisionless systems, which has been fully parallelized and adapted to run in several PC-based processors simultaneously, using the well-known PVM message passing library software. SPH algorithms, not yet included, may be easily incorporated to the code. The code is written in ANSI C; it can be freely downloaded from a public ftp site. Simulations of collisions of galaxies are presented, with which the performance of the code is tested.